Consumption Pattern of Household Street Vendors in Makassar City - Andi Samsir; Muhammad Imam Ma'ruf (Universitas Negeri Makassar, 2019)
Government policy in hacking poverty is still considered not able to reduce the spatial problems such as creating employment in the formal sector or providing representative space (market) to maintain their minimum consumption. The high dependence on PKL business income in maintaining their consumption patterns makes this sector a lot of people are involved in the poor. Based on these problems, the formulation of the problem in this study is first, what is the pattern of household consumption in street vendors in Makassar City. Based on the results of the study, it can be seen that: First, when viewed from the amount of income obtained by the size of the family dependents that are large, most of them can be categorized as non-poor, in the statistical criteria of the Central Bureau of Statistics (BPS). However, for the size of life in Makassar City with the consumer price index (CPI) by referring to the cost of living survey in 2012 most of them could be categorized as relatively low income. Second, this data shows that most of them live below the standard of living in Makassar City. In fact, more than half of them have to live with spending under 3 million rupiah per month. With relatively low income, almost half of the average household expenditure is for food expenditure.